Selective Determination of Tetracycline in Broiler Chicken Meat by Molecularly Imprinted Polymer - Suryana, Shendi; Najihudin, Aji; Elivania, Salma; Suherman, Meillia (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Tetracycline (TC) residues in poultry meat products can create antibiotic resistance in humans who consume them. Hence, sensitive analytical procedures to evaluate the quantities of tetracycline residues are required to assess the safety of these products for consumption. The study aimed to develop a sorbent using molecular imprinting technology to analyze tetracycline in chicken broiler meat products. The study used several tests and computational techniques to increase the effectiveness of screening for the best MIP systems. According to the bond energybased computational analysis, methacrylate acid (MAA) was the best functional monomer at a TC-to-MAA molar ratio of 1:6. The mixture of methanol and chloroform yielded the greatest Ka. The Job plot showed that a TC-to-MAA-molar ratio of 1:6 was best for synthesizing imprinted polymer in the mixture of methanol and chloroform. We generated MIPs using two alternative production methods: bulk (MIP1) and precipitation (MIP2). Adsorption capacity results revealed that MIP1 matches well with the Langmuir model, whereas MIP2 fits better with the Freundlich. MIP1 application produced recovery rates of 82,74±4.1% and MIP2 results of 92.14±3.2% for TC in spike-chicken meat. The outcomes of the selectivity test also demonstrated that MIP2 is superior to MIP1 and can recover TC from spiked chicken meat while coexisting with another antibiotic drug. The study’s findings indicate that MIP2 helps determine TC in spike chicken meat.